Rekonstruksi Doktrin Loss of Chance dalam Gugatan Perdata terhadap Pelaku Child Grooming di Indonesia - Febriansyah Valentino; Muhammad Wildan Majid (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the application of the loss of chance doctrine as a standard for civil compensation for victims of child grooming in Indonesia. The research employs a normative legal method using statutory and conceptual approaches through an examination of the Indonesian Civil Code (KUHPerdata), Law Number 35 of 2014 concerning Child Protection and Supreme Court Regulation (Perma) Number 3 of 2017. The findings reveal a gap between de jure and de facto protection in the restoration of victims’ rights and demonstrate that the loss of chance doctrine can be internalized through a progressive interpretation of Articles 1246 and 1365 of the Indonesian Civil Code by utilizing the formula GR = NKD × KP. This study concludes that the adoption of the doctrine constitutes an organic juridical evolution required by the Indonesian legal system. Therefore, it is recommended that the Supreme Court promptly issue a Supreme Court Circular Letter (SEMA) or a Supreme Court Regulation (Perma) as technical guidelines for judges in quantifying the probabilistic losses suffered by child grooming victims in a standardized manner.